Elastomagnetic nanofiber wires by magnetic field assisted electrospinning - V. Guarino; V. Iannotti; G. Ausanio; L. Ambrosio; L. Lanotte (eXPRESS Polymer Letters)
Magnetic field assisted electrospinning is supplemented by conductive sheets that envelop the magnets and have the same potential as the deposition electrode. By optimizing the experimental conditions, it is possible to produce wires made of polymer nanofibers that incorporate longitudinally oriented magnetic particles. The morphological and magnetic characterizations confirm the preferential orientations. The new nanofiber wires are easily aligned along the maximum intensity line of the applied magnetic field. Moreover, the nanostructured wires have high longitudinal elastomagnetic strain and high transversal deflection as a response to magnetic field stimuli. Therefore, these new threadlike aggregates of magnetic nanofibers could be very appealing for application in all microelectronic or biomedical devices whose functionality requires orientation or deformation.